INFLUENCE OF PRE AND POST EMERGENCE HERBICIDES ON WEED CONTROL, YIELD AND ECONOMICS OF TRANSPLANTED RICE (Oryza sativa L.) - T. RAM PRAKASH, S. ANUSHA, M. MADHAVI, G. PRATIBHA and (The Journal of Research, PJTSAU, 2017)
Rice (Oryza sativa L.) is one of the predominant food crop, a grain of life for more than 70 percent of the Asian population and staple food crop for world’s poorest and densely populated regions. India is the world’s second largest producer (105.3 M t) covering an area of 44.10 M ha, with the productivity level of 2.38 t ha-1 (Department of Agriculture and Cooperation 2014). In Telangana state, rice is grown in 2 M ha with an out turn of 6.6 M t (DES, 2013). Application of preemergence herbicides control weeds only in the early stages of crop growth. In order to control the weeds at later stages, application of postemergence herbicides is necessary, hence there is a need to apply herbicides in sequence in order to control weeds effectively.